Chromosome-level genome and high nitrogen stress response of the widespread and ecologically important wetland plant Typha angustifolia - Liao, Yang; Zhao, Shuying; Zhang, Wenda; Zhao, Puguang; Lu, Bei; Moody, Michael L.; Tan, Ninghua; Chen, Lingyun (Frontiers in Plant Science, 2023)
Typha angustifolia L., known as cattail, is widely distributed in Eurasia but has been introduced to North America. The plant is aquatic or semi-aquatic and ecologically important. The plant is a traditional medicinal herb and is commonly used in phytoremediation. To provide a high-quality genome of Typha angustifolia and investigate genes in response to high nitrogen stress, we carried out complete genome sequencing and high-nitrogen-stress experiments. We generated a chromosomal-level genome of T. angustifolia, which had 15 pseudochromosomes, a size of 207 Mb, and a contig N50 length of 13.57 Mb. Genome duplication analyses detected no recent whole-genome duplication (WGD) event for T. angustifolia. An analysis of gene family expansion and contraction showed that T. angustifolia gained 1,310 genes and lost 1,426 genes. High-nitrogen-stress experiments showed that a high nitrogen level had a significant inhibitory effect on root growth. Differential gene expression analyses using 24 samples found 128 differentially expressed genes (DEGs) between the treated and control groups. DEGs in the roots and leaves were enriched in alanine and aspartate, as well as the glutamate metabolism, nitrogen metabolism, photosynthesis, phenylpropanoid biosynthesis, plant-pathogen interaction, and mitogen‑activated protein kinase pathways. This study provides genomic data for a medicinal and ecologically important herb and lays a theoretical foundation for plant-assisted water pollution remediation.